2016
DOI: 10.1016/j.ajpath.2015.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Galectin-3 Expression Is Associated with Remodeling of the Pressure-Overloaded Heart and May Delay the Hypertrophic Response without Affecting Survival, Dysfunction, and Cardiac Fibrosis

Abstract: The b-galactosideebinding animal lectin galectin-3 is predominantly expressed by activated macrophages and is a promising biomarker for patients with heart failure. Galectin-3 regulates inflammatory and fibrotic responses; however, its role in cardiac remodeling remains unclear. We hypothesized that galectin-3 may be up-regulated in the pressure-overloaded myocardium and regulate hypertrophy and fibrosis. In normal mouse myocardium, galectin-3 was constitutively expressed in macrophages and was localized in at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
85
1
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(94 citation statements)
references
References 50 publications
0
85
1
8
Order By: Relevance
“…A recent study, however, suggested that macrophages are not the only source of Gal-3 in the myocardium in a mouse model of transverse aortic constriction. 31 Early upregulation of Gal-3 after pressure overload was localized in subpopulations of macrophages and myofibroblasts. Of note, after 1 to 4 weeks of transverse aortic constriction, a subset of cardiomyocytes in fibrotic areas contained large amounts of Gal-3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study, however, suggested that macrophages are not the only source of Gal-3 in the myocardium in a mouse model of transverse aortic constriction. 31 Early upregulation of Gal-3 after pressure overload was localized in subpopulations of macrophages and myofibroblasts. Of note, after 1 to 4 weeks of transverse aortic constriction, a subset of cardiomyocytes in fibrotic areas contained large amounts of Gal-3.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, after 1 to 4 weeks of transverse aortic constriction, a subset of cardiomyocytes in fibrotic areas contained large amounts of Gal-3. 31 Further studies are needed to clarify whether inflammatory cells are indeed the source of myocardial Gal-3 in iCMP and which type of cell is responsible for it.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have shown that GAL-3 is not a critical modulator of cardiac fibrosis but may delay the hypertrophic response and further studies are needed to clearly establish its role [36]. Interestingly, in patients with HFpEF, there was a statistically significant correlation between adiponectin and MMP-2 with the E/E' and an inverse correlation of PIIINP with E/A.…”
Section: Discussionmentioning
confidence: 90%
“…Gal-3 is expressed predominantly by fibroblasts and macrophages in the majority of previous studies [20][21][22]. However, some also reported that Gal-3 is expressed in ventricular myocytes in a pressure-overloaded remodeling heart model and that a high density of Gal-3-positive myocytes is related to abnormalities in remodeling and heart function [23]. Furthermore, HL-1 cells have been demonstrated to express Gal-3 at baseline and remarkably induce its expression following protein kinase C activation, indicating that cardiomyocytes may also act as a source of Gal-3 in the heart [24] and possibly be greatly induced in pathological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this result, we found that the TGF-β1/α-SMA/Col I pathway was induced in neonatal rat cardiac fibroblasts by Gal-3-enriched conditioned HL-1 culture media, and further confirmed the role of Gal-3 in fibroblast differentiation and proliferation with recombinant human Gal-3 protein treatment, both at 10 and 30 μg/mL; exogenous Gal-3 activated the profibrotic pathway and induced fibroblast proliferation, as detected by CCK-8. All of these results led us to the conclusion that although cardiomyocytes barely express Gal-3 under physiological conditions [9], under pathological conditions, cardiomyocytes may also act as an alternative source of Gal-3 [23,24], inducing fibroblasts to synthesize collagen and other pro-fibrotic components of the extracellular matrix.…”
Section: Discussionmentioning
confidence: 99%